Yaylı tanbur metodu ve temel üslûbu giriş - Ünal, Mehmet (My University, 2019)
Bu çalışmanın amacı Yaylı Tanbur çalınma sistemini kolaydan zora olacak şekilde düzenleyerek, öğrenmek isteyenlere temel bir kılavuz oluşturabilmektir. Bu minvalde öğrencinin yaylı tanburu öğrenebilmesi için, temel egzersizlerin yanı sıra üslup ve süsleme bilgileri ile birlikte bu hususları öğrenmeyi pekiştirecek olan, her kesimin aşina olduğu, şarkılara, ilâhilere, saz semâîsi ve peşrevlere ve akabinde Türk Mûsikîsinde trasnpoze çalışmasına yer verilmiştir.

The aim of this work by spring Tanbûri methodological design sense, is tocreate a basic guide for tho sew howant to learn. In order to learn the student's spring drum in this manner, which together with basic exercises as well as the style and authority information to rein force learning these matters, he is familiar with all sections of song sand hymnsto, Saz Semâî and overture and then the Turkish music authority of the division, which is the best way to exercise with reed study examples are included.
Keywords: Dini açıdan; fundamental styles; History; Islam; Islamic music; İslam; İslami müzik; Metod; Metot; Music; Müzik; Religious aspects; spring tanbur; Tanbur; Tanbur Yaylı Tanbur; Tarih; Turkey; Türkiye; Yaylı Tanbur